Additive-driven microwave crystallization of tyramine polymorphs and salts: a quantum crystallography perspective - Szymon Grabowski; Klaudia Nowakowska; Helena Butkiewicz; Anna Hoser; Aleksandra Wesełucha-Birczyńska; Tomasz Seidler; Paulina Moskal; Marlena Gryl (IUCrJ)
Polymorphism – the ability of a compound to exist in multiple crystalline forms – needs to be carefully considered in the design of functional materials, particularly in the context of cocrystallization. Tyramine, a biogenic amine, is a promising candidate for polymorph exploration due to its conformational flexibility and ability to form salts. In this study, we investigate the crystallization of tyramine polymorphs using additives and microwave-assisted techniques. Our findings reveal the formation of a new tyramine polymorph and two distinct salts, highlighting the impact of microwave radiation and additive-driven crystallization on polymorph stability and molecular encapsulation. The study demonstrates that the triclinic tyramine polymorph (T2) is thermodynamically more stable due to its lower electronic energy, whereas the monoclinic form (T1) features slightly stronger intermolecular interactions. Over time, in solution, crystals of barbital–tyramine salts (C1 and C2) begin to form, providing an opportunity to assess structural evolution. Optical properties calculations show significant maximum linear birefringence values (0.164 and 0.255) for two polymorphs of tyramine, whereas for C1, this value decreases to 0.095.